Product Quality and Brand Image on The Purchase Decision of Sari Roti Clear Bread with Customer Satisfaction as a Moderating Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the effect of product quality and brand image on purchasing decisions of Sari Roti white bread in Pati Regency, with customer satisfaction as a moderating variable. The phenomenon of fluctuating Sari Roti sales during the 2020–2024 period indicates challenges in maintaining market share amid increasingly fierce competition in the packaged bread industry.This research employs a quantitative approach with a survey method. The sample consists of 200 respondents selected using purposive sampling with the criterion of having purchased Sari Roti white bread at least once. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares (PLS) with the SmartPLS 4.0 application, as well as Moderated Regression Analysis (MRA). The results of the study show that product quality has a positive and significant effect on purchasing decisions, and brand image also has a positive and significant effect on purchasing decisions. The moderation test reveals that customer satisfaction does not moderate the effect of product quality on purchasing decisions, but it does moderate the effect of brand image on purchasing decisions. This research is expected to serve as a reference for companies in formulating marketing strategies that focus on product quality and customer satisfaction management in order to maintain loyalty and increase purchasing decisions.
Keywords: product quality, brand image; purchasing decision; customer satisfaction